Management Methods of Agro Market through Digital Platforms - Mamatmuminov Abdulla (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the role of digital platforms in modernizing the agricultural sector and improving the management efficiency of the agro market. The study explores how digital technologies contribute to agricultural product circulation, price stability, information exchange among market participants, and rational resource utilization. The research focuses on the prospects of digital transformation in the agro market within Uzbekistan’s context.